2017
DOI: 10.1021/jacs.7b06287
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Substitution of K+ Sites in Cyclodextrin Metal–Organic Frameworks by Li+ Ions

Abstract: Co-crystallization of K and Li ions with γ-cyclodextrin (γ-CD) has been shown to substitute the K ion sites partially by Li ions, while retaining the structural integrity and accessible porosity of CD-MOF-1 (MOF, metal-organic framework). A series of experiments, in which the K/Li ratio was varied with respect to that of γ-CD, have been conducted in order to achieve the highest possible proportion of Li ions in the framework. Attempts to obtain a CD-MOF containing only Li ions resulted in nonporous materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 43 publications
0
68
0
Order By: Relevance
“…Naturally occurring γ-cyclodextrin (γ-CD) have been successfully used in building CD-MOFs with permanent porosity and the ability to store small molecules in their pores. [13][14][15] Recently, we have communicated the use of CDs combined with inorganic polyoxometalates (POMs) [16][17][18] as MBBs to prepare a new generation of porous hybrid frameworks (POM-CD MOFs). 19 These assemblies benefited from the intrinsic microporosity and functional multiplicity of both isolated building blocks.…”
mentioning
confidence: 99%
“…Naturally occurring γ-cyclodextrin (γ-CD) have been successfully used in building CD-MOFs with permanent porosity and the ability to store small molecules in their pores. [13][14][15] Recently, we have communicated the use of CDs combined with inorganic polyoxometalates (POMs) [16][17][18] as MBBs to prepare a new generation of porous hybrid frameworks (POM-CD MOFs). 19 These assemblies benefited from the intrinsic microporosity and functional multiplicity of both isolated building blocks.…”
mentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) based on cyclodextrin were developed by the Stoddart group and have been known for almost ten years (Smaldone et al, 2010). Many cyclodextrin MOFs with various alkali metal ions have been obtained so far (Patel et al, 2017;Bagabas et al, 2013). Exceptions are lithium ion-based MOFs because all of the compounds obtained that have been reported in the literature contain two different metal ions in the crystal structure (Bagabas et al, 2013;Patel et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Many cyclodextrin MOFs with various alkali metal ions have been obtained so far (Patel et al, 2017;Bagabas et al, 2013). Exceptions are lithium ion-based MOFs because all of the compounds obtained that have been reported in the literature contain two different metal ions in the crystal structure (Bagabas et al, 2013;Patel et al, 2017). Lithiumbased MOFs are among the best candidates for electrode materials for lithium-ion batteries because of their high porosity and structural control (Baumann et al, 2019;Sharma et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The high volatility associated with CO 2 BOLs and the hardship of drying/handling, together with the high corrosive character, paved the way toward single component CO 2 BOLs 17 ( Scheme 1C ) that unfortunately exhibited high viscosity upon chemisorption. Afterwards, Sir J. F. Stoddart’s group 41 44 reported that the hydroxyl groups located at the rim of γ-cyclodextrin-based metal–organic frameworks (CD-MOFs) are capable of reacting with CO 2 reversibly to form a metal-stabilized organic alkyl-carbonate (a detailed discussion is provided, vide infra ).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in synthesizing CD-MOFs with cations other than K + , Rb + and Cs + , is the inability to obtain porous, crystalline frameworks. Very recently, Patel et al 44 demonstrated the partial substitution of K + with Li + through co-crystallizing KOH and LiOH with γ-CD. As shown in Table 1 , the most stable Li/K–CD-MOF with the highest Li + : K + ratio (0.61 : 1.18) had a comparable Brunauer–Emmett–Teller (BET) surface area and a characteristic better sorption in comparison with those obtained for other iso-structural CD-MOFs.…”
Section: Introductionmentioning
confidence: 99%